In Situ High-Resolution Transmission Electron Microscopy (TEM) Observation of Sn Nanoparticles on SnO2 Nanotubes Under Lithiation. (8th December 2017) - Cheong, Jun Young; Chang, Joon Ha; Kim, Sung Joo; Kim, Chanhoon; Seo, Hyeon Kook; Shin, Jae Won; Yuk, Jong Min; Lee, Jeong Yong; Kim, Il-Doo
Abstract: We trace Sn nanoparticles (NPs) produced from SnO2 nanotubes (NTs) during lithiation initialized by high energy e-beam irradiation. The growth dynamics of Sn NPs is visualized in liquid electrolytes by graphene liquid cell transmission electron microscopy. The observation reveals that Sn NPs grow on the surface of SnO2 NTs via coalescence and the final shape of agglomerated NPs is governed by surface energy of the Sn NPs and the interfacial energy between Sn NPs and SnO2 NTs. Our result will likely benefit more rational material design of the ideal interface for facile ion insertion.